Pengaruh Permainan Target Terhadap Kemampuan Shooting di Club Sepakbola Remaja Bhayangkara Sungai Rotan Kabupaten Muara Enim - Simanungkali, Janward Gunawan; Yadi, Farhan; Mahendra, Agung (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to determine how much influence the target game has on the shooting ability of players at the Bhayangkara Youth Football Club Sungai Rotan, Muara Enim Regency. The formulation of the problem in this study is: Is there an effect of target games on the shooting abilities of players at the Bhayangkara Sungai Rotan Youth Football Club, Muara Enim Regency? This research method is a quasi-experimentalresearch with the design or treatment design used as